Implementasi Program Anti Bullying pada Sekolah Ramah Anak di SMAN 1 Brebes Kabupaten Brebes - Puspitarini, Yeni; Wuryandini, Endang; Rasiman, Rasiman (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
This research is motivated by the implementation of an anti-bullying program in schools that has been running at SMAN 1 Brebes. This program is implemented in the learning process that can be internalized in Character Education at SMAN 1 Brebes. The purpose of this study was to determine 1) the planning of an anti-bullying program in a child-friendly school at SMAN 1 Brebes, 2) the implementation of an anti-bullying program in a child-friendly school at SMAN 1 Brebes, and 3) the evaluation of an anti-bullying program in a child-friendly school at SMAN 1 Brebes, by analyzing the implementation of the anti-bullying program in a child-friendly school. This study explores the effectiveness of the program in creating a safe and conducive environment for students, as well as reducing bullying behavior in schools. The method used in this study is qualitative descriptive research using data collection instruments in the form of observation, interview, and documentation methods. Data analysis used through the process of data collection, data reduction, data presentation and drawing conclusions, while data validity uses data triangulation. The results of the study indicate that the implementation of an anti-bullying program that is applied comprehensively and sustainably can reduce bullying incidents significantly. Key success factors include teacher training, student involvement in preventive activities, and full support from the school and parents. In addition, clear policies and consistent disciplinary action against bullies play a role in creating child-friendly schools. The conclusion of this study is that the implementation of anti-bullying programs in child-friendly schools has a significant positive impact on student well-being and the overall school climate. Recommendations are provided for further development of this program, including increased training for teachers and school staff, and increased parental and community involvement in preventive efforts.